Analisis titik impas keuangan sebagai penentu harga dasar proyek konstruksi cme (civil, mechanical and electrical) atas pembangunan infrastruktur menara telekomunikasi area Jawa Timur (Studi pada perusahaan konstruksi) - Vinanti, Siona (Kajian Ilmiah Mahasiswa Manajemen, 2015)
The main purpose the establishment of a construction company to benefit so that it requires that management has a clear business development orientation. To achieve maximum profit necessary management capabilities to be able to analyze the feasibility of the project to determine the base price of the project so as to win the tender and competing with similar companies. The basic price of projects is an important element in the management of projects costs, in determining the base price of projects required a financial break-even point analysis. This study uses a case study on the construction company PT Muara Karya and the method using expost facto approach. The results of the analysis states that the calculation of the projects contract in 2008-2010 and in 2013 had reached a financial break-even point, while the contract in 2011-2012 is not reached financial breakeven point so that the company does not make a profit and losing.